Profitability analysis of prawn industry in Pontevedra, Capiz. - Tambaoan, Tala C (2000.)
The study describes the pond practices and farm management of prawn culture in Pontevedra, Capiz. The cost structure and the profit level are computed by method of culture - extensive, modified extensive and semi - intensive. The method of analysis used on profitability is Cost and Return Analysis. (p)Pond practices and farm management include pond preparation, stocking, feeding, harvesting, pre-sale activities and pricing. Semi-intensive has the highest costs on total fixed costs, total variable costs and total opportunity cost. Extensive has the lowest costs on total fixed costs, total variable costs and total opportunity costs. Semi-intensive is the highest in revenue, followed by modified extensive and extensive. Modified extensive on the other hand has the highest rate of return on investment followed by extensive and semi-intensive. (p)In improving the yield, extensive culture must have good pond preparation. Modified extensive and semi-intensive should have good pond preparation and high quality of supplemental feeds to improve its yield since heavier weight of prawns mean higher prices. All culture techniques should stock quality of fry for higher survival rate.
Research Project (Undergraduate, Bachelor of Arts in Economics-Management) College of Arts and Sciences, UP Visayas, Miagao, Iloilo
Keywords: Prawn Industry -- Pontevedra, Capiz